Flow mediated dilatation and the progression of abdominal aortic aneurysms - Lee, R; Bellamkonda, K; Jones, A; Killough, N; Woodgate, F; Williams, M; Cassimjee, I; Handa, A (Elsevier, 2017)
Objective/Background Biomarker(s) for prediction of the future progression rate of abdominal aortic aneurysms (AAA) may be useful to stratify the management of individual patients. AAAs are associated with features of systemic inflammation and endothelial dysfunction. Flow mediated dilatation (FMD) of the brachial artery is a recognised non-invasive measurement for endothelial function. We hypothesised that FMD is a potential biomarker of AAA progression and reflects the temporal changes of endothelial function during AAA progression. Methods In a prospectively recruited cohort of patients with AAAs (Oxford Abdominal Aortic Aneurysm Study), AAA size was recorded by antero-posterior diameter (APD) (outer to outer) on ultrasound. Annual AAA progression was calculated by (ΔAPD/APD at baseline)/(number of days lapsed/365 days). FMD was assessed at the same time as AAA size measurement. Analyses of data were performed in the overall cohort, and further in subgroups of AAA by size (small: 30–39 mm; moderate: 40–55 mm; large: > 55 mm). Results FMD is inversely correlated with the diameter of AAAs in all patients (n = 162, Spearman's r = −.28, p < .001). FMD is inversely correlated with AAA diameter progression in the future 12 months (Spearman's r = −.35, p = .001), particularly in the moderate size group. Furthermore, FMD deteriorates during the course of AAA surveillance (from a median of 2.0% at baseline to 1.2% at follow-up; p = .004), while surgical repair of AAAs (n = 50 [open repair n = 22, endovascular repair n = 28)] leads to an improvement in FMD (from 1.1% pre-operatively to 3.8% post-operatively; p < .001), irrespective of the type of surgery. Conclusion FMD is inversely correlated with future AAA progression in humans. FMD deteriorates during the natural history of AAA, and is improved by surgery. The utility of FMD as a potential biomarker in the context of AAA warrants further investigation.